Hilar and Mediastinal Involvement in Bronchogenic Carcinoma: CT Evaluation and Histopathologic Correlation (Bangladesh Journal of Nuclear Medicine, 2018)
This cross sectional study was done to assess the diagnostic accuracy of Computed Tomography (CT) in the evaluation of hilar and mediastinal involvement in bronchogenic carcinoma. A total of 104 patients with bronchial mass lesion were included in the study. Thorough history, clinical examinations, X-ray chest, CT chest and CT guided fine needle aspiration cytology (FNAC) were done. This study was carried out in the department of Radiology and Imaging of Bangabandhu Sheikh Mujib Medical University (BSMMU) and Dhaka Medical College Hospital (DMCH) from July 2009 to June 2010. Diagnosis of hilar and mediastinal involvement in bronchogenic carcinoma by CT scan was highly sensitive and specific. CT findings of the present study correlated well in most of the cases with the CT guided FNAC results. It can therefore be concluded that CT scan is a useful modality in the evaluation of hilar and mediastinal involvement in bronchogenic carcinoma.Bangladesh J. Nuclear Med. 19(1): 32-37, January 2016